Correction: Comparative study of three heteropolyacids supported on carbon materials as catalysts for ethylene production from bioethanol. Issue 3 (16th January 2019) - Almohalla, M.; Rodríguez-Ramos, I.; Guerrero-Ruiz, A.
Abstract : Correction for 'Comparative study of three heteropolyacids supported on carbon materials as catalysts for ethylene production from bioethanol' by M. Almohalla et al., Catal. Sci. Technol., 2017, 7, 1892–1901.